2017
DOI: 10.1177/1479972317745733
|View full text |Cite
|
Sign up to set email alerts
|

Dose uniformity of budesonide Easyhaler® under simulated real-life conditions and with low inspiration flow rates

Abstract: Budesonide Easyhaler® multidose dry powder inhaler is approved for the treatment of asthma. Objectives were to determine the delivered dose (DD) uniformity of budesonide Easyhaler® in simulated real-world conditions and with different inspiration flow rates (IFRs). Three dose delivery studies were performed using 100, 200, and 400 µg/dose strengths of budesonide. Dose uniformity was assessed during in-use periods of 4–6 months after exposure to high temperature (30°C) and humidity (60% relative humidity) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…Furthermore, study physicians reported that use of the Bufomix Easyhaler ® was easy to teach, with their patients learning inhaler use quickly. Our data support previous patient preference data (based on studies in children and adults) that demonstrated the Easyhaler ® was easy to teach, learn and use, coupled with more user satisfaction [ 18 , 32 ]; findings were recently confirmed by a meta-analysis [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, study physicians reported that use of the Bufomix Easyhaler ® was easy to teach, with their patients learning inhaler use quickly. Our data support previous patient preference data (based on studies in children and adults) that demonstrated the Easyhaler ® was easy to teach, learn and use, coupled with more user satisfaction [ 18 , 32 ]; findings were recently confirmed by a meta-analysis [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…The Bufomix Easyhaler ® has demonstrated similar in vitro flow rate dependency compared with the Turbuhaler ® , using clinically relevant air flow rates collected from patients with asthma and COPD [ 18 ]. Additionally, superior dose consistency was observed compared with the Turbuhaler ® at different clinically relevant in vitro flow rates [ 19 ]. Therapeutic equivalence and equivalent bronchodilator efficacy have also been reported between the two inhalers [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A pooled analysis of two randomized, multicenter, crossover, open-label studies in patients aged 6-88 years with asthma (n = 287) or COPD (n = 96) found that by using the Easyhaler, most could achieve or exceed a peak inspiratory flow rate of 30 l/min, which is the minimum required to ensure optimal and consistent dose delivery [36]. Recent dose uniformity analyses also confirmed consistent delivered dose using the Easyhaler under simulated real-world conditions and a variety of inspiratory flow rates [37].…”
Section: Discussionmentioning
confidence: 88%
“…Easyhaler TM (EH) (Orion Corporation, Finland), is a three-step, light, compact, and user-friendly DPI. It has advantages over older DPIs [6], including dose uniformity in different real-world conditions [7]. With regard to features such as perception of inhalation, size, discreetness, mouthpiece comfort, and dose counter, EH was rated higher than other inhaler devices by asthma patients [8].…”
Section: Introductionmentioning
confidence: 99%